EFL Students’ Preferences for Corrective Feedback in Speaking Instruction across Speaking Course Levels - Atma, Nurul; Widiati, Utami (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
This cross-sectional survey study investigates the preferences of freshmen and sophomores for corrective feedback in speaking instruction, including their perceptions of corrective feedback, the types of errors to be corrected, the timing of correction, the sources of correction, and the types of corrective feedback. Using questionnaires and interviews to collect the data, the study found that both groups welcomed corrective feedback, acknowledged its benefits, but felt embarrassed when corrected orally. Both freshmen and sophomores wanted all of their errors to be corrected. Whereas the freshmen preferred grammatical errors to be corrected consistently, the sophomores preferred phonological errors to be prioritized. Regarding the timing of correction, both groups expected their errors to be corrected after they had finished speaking. In addition, both groups preferred teacher feedback over other sources of feedback. Finally, regardless of the type of error, the most preferred type of corrective feedback was explicit feedback, whereas the least preferred was the use of paralinguistic signals.